Auditory Subjective-Straight-Ahead Blurs during Significantly Slow Passive Body Rotation. (January 2022) - Honda, Akio; Tsunokake, Sayaka; Suzuki, Yôiti; Sakamoto, Shuichi
This paper reports on the deterioration in sound-localization accuracy during listeners' head and body movements. We investigated the sound-localization accuracy during passive body rotations at speeds in the range of 0.625–5 °/s. Participants were asked to determine whether a 30-ms noise stimuli emerged relative to their subjective-straight-ahead reference. Results indicated that the sound-localization resolution degraded with passive rotation, irrespective of the rotation speed, even at speeds of 0.625 °/s.